Changes in Intestinal Flora and Metabolites in Neonates With Breast Milk Jaundice - Li, Yaxuan; Shen, Nan; Li, Jing; Hu, Rui; Mo, Xi; Xu, Liqing (Frontiers in Pediatrics, 2020)
Background: Breast milk jaundice (BMJ) is the first cause of neonatal jaundice, however its underlying mechanism is yet to be deciphered. We conducted a study to investigate intestinal flora in neonates with BMJ and used metabolomics to decipher the possible mechanisms by which intestinal flora induces jaundice. Methods: Microbiota collected from the feces of BMJ patients and jaundice-free breastfeeding newborns was used for 16S rRNA sequencing. In addition, differences in fecal metabolites were analyzed using gas chromatography mass spectrometry (GC/MS). The relationship between intestinal microbiota and the differences in fecal metabolites was then analyzed. Results: There was no significant difference in the richness and diversity of intestinal flora between BMJ and the control group; however, there were differences in the structure. At the phylum level, the relative abundance of Firmicutes was higher in the control group compared to the BMJ group, whereas Proteobacteria was higher in the infants with BMJ. Additionally, at the genus level, the relative abundance of Haemophilus was higher in control group; while the relative abundances of Escherichia, Morganella and Rothia were lower. More remarkably, the major differences in metabolites between the two groups were glyceric acid, succinic acid, and phenylalanine. Additionally, the abundance of Escherichia was positively correlated with succinic acid and cadaverine levels. Conclusions: The intestinal flora colonization status in BMJ patients is immature. This study reports for the first time the study of intestinal flora, especially Escherichia, play an important role in BMJ, and found it may be associated with the regulation of succinic acid metabolic pathways.